Numerical study on the effect of pressure and nozzle dimension on particle distribution and velocity in laser cladding under vacuum base on CFD. (August 2016) - Zhang, Baicheng; Coddet, Christian
Highlights: The first time simulation work in laser cladding process under vacuum. A optimized nozzle dimension is proposed by simulation method. A convergence powder flow can be found in LC process under vacuum. The carrier gas as Helium can lead to an over high particle velocity. Abstract: Numerical study was conducted to investigate the effect of environment pressure and nozzle dimensions on particle distribution and velocity in laser cladding by using three-dimensional models based on computational fluid dynamics. The simulation results show that the vacuum environment can lead to a high particle velocity and convergent powder flow during laser cladding. It was found that the nozzle dimensions have significant effect on particle distribution and velocity. A more convergent powder flow can be obtained when used 60° nozzle degree. Moreover, by decreasing the focus length, the powder flow concentration can be increased, which results in a high powder feeder delivery efficiency. In additional, the Helium carrier gas can steeply accelerate the particle to a high velocity during laser cladding process under vacuum.